2006
DOI: 10.1038/nature04505
|View full text |Cite
|
Sign up to set email alerts
|

Episodic growth of the Gondwana supercontinent from hafnium and oxygen isotopes in zircon

Abstract: It is thought that continental crust existed as early as 150 million years after planetary accretion, but assessing the rates and processes of subsequent crustal growth requires linking the apparently contradictory information from the igneous and sedimentary rock records. For example, the striking global peaks in juvenile igneous activity 2.7, 1.9 and 1.2 Gyr ago imply rapid crustal generation in response to the emplacement of mantle 'super-plumes', rather than by the continuous process of subduction. Yet unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
261
1
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 667 publications
(277 citation statements)
references
References 32 publications
10
261
1
5
Order By: Relevance
“…In contrast, Hf-T DM 3 calculated with a mafic crustal precursor yield ages of 1.07-1.19 Ga, some 100-200 Ga older than the major crystallization events recorded in the ANS. Nevertheless, in accordance with Hawkesworth and and Kemp et al (2006), such discrepancies may simply reflect an older crustal formation event at 1.1-1.2 Ga, when zircon-free mafic material was extracted from the mantle, whereas younger events (*870-550 Ma) represent reworking of this lower crust (e.g., crustal differentiation of Kemp et al 2006). Future analysis of Hf isotopes in zircons from rocks of more southerly regions within the ANS may help to resolve this problem.…”
Section: Hf and Nd Model Agessupporting
confidence: 82%
See 1 more Smart Citation
“…In contrast, Hf-T DM 3 calculated with a mafic crustal precursor yield ages of 1.07-1.19 Ga, some 100-200 Ga older than the major crystallization events recorded in the ANS. Nevertheless, in accordance with Hawkesworth and and Kemp et al (2006), such discrepancies may simply reflect an older crustal formation event at 1.1-1.2 Ga, when zircon-free mafic material was extracted from the mantle, whereas younger events (*870-550 Ma) represent reworking of this lower crust (e.g., crustal differentiation of Kemp et al 2006). Future analysis of Hf isotopes in zircons from rocks of more southerly regions within the ANS may help to resolve this problem.…”
Section: Hf and Nd Model Agessupporting
confidence: 82%
“…9. Hf-T DM 1 ages provide the minimum estimate for crustal formation events (e.g., Kemp et al 2006) in the Hf isotope system. Hf-T DM 1 ages calculated for CA2 and AL rocks of the SE-region (excluding the Sharm pluton) yield an average of 0.89 Ga and show marked correlation with Nd-T DM 2, but not with Nd-T DM 1 (Fig.…”
Section: Hf and Nd Model Agesmentioning
confidence: 99%
“…[33] Notably, the curves of Figure 5 qualitatively resemble those of observed episodic continental growth [Condie, 1998;Kemp et al, 2006]. Parman [2007] showed that not only the production peaks of OIB but also those of MORB can be correlated to the zircon-age peaks.…”
Section: Episodic Growth Of the Continental Crustsupporting
confidence: 51%
“…The timing of generation of continents has been debated by Taylor and McLennan [1995] and Bowring and Housh [1995]. Condie [2000] and Kemp et al [2006] show that the total volume of continents did not originate as a whole at the beginning of the Earth's thermal evolution but by repeated differentiation cycles. Only about one half of the present total volume was produced by chemical differentiation until the end of the Archean, 2500 Ma ago.…”
Section: Generation and Episodic Growth Of Continents: Observationsmentioning
confidence: 99%
“…However, zircons crystallized from a mixed source magma which involves a sedimentary cycle or hydrothermal alteration have elevated δ 18 O values [60,61]. Thus, combination of Hf and O isotopes can be used to distinguish zircons derived from a mantle sources or a crustal source region with a high sedimentary component [4,62].…”
Section: Implications For Early Precambrian Crustal Evolution In the Nccmentioning
confidence: 99%